INTERFERENSI BAHASA MAKASSAR TERHADAP BAHASA INDONESIA DALAM BERKOMUNIKASI SISWA KELAS V SD INPRES PARANG BERU KABUPATEN GOWA - Nurul Ariqa Ainunnisa; Haslinda; Syekh Adi Wijaya Latief (STKIP Subang, 2024)
The main problem in this study is how the interference of the language of Makassar to the Indonesian language influences Gaul language on the use of Indonesia language in the environment of the school class V SD Inpres Parang Beru district of Gowa. Research procedures include data collection, data reduction, data presentation, and conclusion drawings. The subjects of this study are students of the V class of SD Inpres Parang Beru district of Gowa of 5 people. The results of the study showed that the interference of the language of Makassar to the Indonesian language in communicating students among students in particular in the SD Inpress Parang Beru district Gowa. This can be seen in interferences that occur, such as phonological interference, which is a change in the initial and middle words of the sound. In morphological interference there is the use of confirming clitics namely proclitic and encryptic.